Liver Ischemia After Transarterial Embolization for Hepatic Trauma Injury - Meng-Lin Han; Chia-Hsun Lu (Diagnostics)
Transarterial embolization (TAE) is a routine procedure performed by interventional radiologists to manage traumatic hepatic injuries. Hepatic super-selective TAE rarely results in ischemia within the embolized area. In this case, the initial CT scan revealed significant contrast extravasation, leading to an urgent TAE. Due to continued concerns about bleeding, a second TAE was performed two days later. Subsequent CT scans revealed localized ischemia and necrosis following increased abdominal pain and elevated liver functions. Further analysis identified a common hepatic artery variation in this case. Thus, the ischemia in segments 6 and 7 was determined to be unrelated to the embolization procedure. A detailed review of the CT images suggests that injury to the accessory right inferior hepatic veins (IHVs) likely caused ischemia and eventual necrosis in segments 6 and 7. While hepatic vein variations are not uncommon, this case highlights the importance of evaluating the condition of hepatic veins, in addition to the hepatic artery and portal vein, during preoperative planning. If no arterial extravasation is identified, conservative treatment may be an option for the patient. Further research on this topic is warranted.